Tobacco cessation after head and neck cancer diagnosis is an independent predictor of treatment response and long-term survival. (November 2022) - Krutz, Matthew; Acharya, Pawan; Chissoe, Geraldine; Raj, Vijay; Driskill, Lane; Krempl, Greg; Zhao, Daniel; Mhawej, Rachad; Queimado, Lurdes
Highlights: Quitting smoking after HNSCC diagnosis increases therapy response by about 4-fold. Quitting after diagnosis reduces cancer recurrence and increases disease-free survival. Smokers at cancer diagnosis who quit before therapy increase long-term survival. Smoke cessation after cancer is predictive of higher therapy efficacy and survival. Abstract: Head and neck squamous cell carcinoma (HNSCC) patients who are current smokers when diagnosed have inferior clinical outcomes compared to never-smokers or previous smokers. However, the impact of quitting after HNSCC diagnosis has not been quantified. In this retrospective, case-control study (n = 134), the odds of complete response to first-line therapy were 3.7 times higher among smokers at diagnosis who quit before treatment initiation (quitters; n = 55) than among those continuing to smoke (p = 0.03). Disease-free survival was also higher among quitters (aHR, 0.33; 95 % CI, 0.12–0.90; p = 0.029). Quitters were 67 % less likely to die of all causes than active smokers (aHR, 0.33; 95 % CI, 0.15–0.71; p = 0.004). These data show for the first time that, smoking cessation after HNSCC diagnosis is predictive of higher therapy efficacy and long-term survival.